ProteoKnight: phage virion protein classification with CNN and uncertainty quantification - Bhuiyan, Abir Ahammed; Neha, Samiha Afaf; Khan, Md. Ishrak (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.